Takayasu arteritis presenting as renovascular hypertension with hypertensive encephalopathy - Tanwar, Vikram Singh; Saini, Anjali; Singh, Anurag Ambroz; Tank, Rakesh (Journal of Advances in Internal Medicine, 2017)
Takayasu arteritis is a large vessel vasculitis that has variable presentation. It is suspected when there are pulse and BP discrepancies between upper limbs or absent pulses. We here presenting a case of takayasu arteritis that remained undiagnosed till 40 years and at first time manifested with hypertensive encephalopathy and managed well with medical therapy. Journal of Advances in Internal Medicine 2017;06(02):35-37.